Influence of Low and High-Protein Diets on Body Growth and Glucose Intensity in Rattus Norvagicus - TAPAS KUMAR MANDAL; NARGISH PARVIN; ASHOK. K. SAXENA; SABYASACHI SARKAR (International Journal of Pharma and Bio Sciences, 2010)
The influence of the protein content of the diet on glucose concentration (denoted by fluorescence intensity) and body weight was studied in the white rat. Rats of 30d of age received ad lib. a control diet containing 15% crude protein (Pl5), or a diet containing 23% crude protein (P23) or 35% crude protein (P35) and a fourth group of rats (P8) received the 8% crude protein contained diet. After 4 week on these diets, plasma glucose intensity and body weight were different in treatment groups P35, P23, P8 and control PI5 rats, but were lower in P8 rats. It is concluded from these studies that these types of dietary manipulation have a significant effect on plasma glucose intensity. Plasma glucose intensity was measured after the 28 days crude protein percentage diet treating by Benedict reagent and fluorescence spectrometry (Perkin Elmer LS 55).